Natal do Educaprev: educação em saúde em um abrigo do município de Jaboticabal/SP - Gonçalves, Ana Carolina Siqueira [UNESP]; Grisólio, Ana Paula Rodomilli [UNESP]; Bastos, Carla Resende [UNESP]; Cruz, Carolina Alvarenga [UNESP]; da Silva, David Attuy Vey [UNESP]; de Moraes, Fernanda Cassioli [UNESP]; Rossi, Gabriel Augusto Marques [UNESP]; de Souza Almeida, Henrique Meiroz [UNESP]; Silva, Higor Oliveira [UNESP]; Gatto, Igor Renan Honorato [UNESP]; Ribeiro, Laryssa Freitas [UNESP]; Picinato, Mirelle Andréa de Carvalho [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
Given that the main purpose of health education is to transfer information to the population, and considering the important role that children play as knowledge multipliers in society, the objective of the “EducaPrev Christmas” project was to promote the interaction of postgraduate students from the Department of Preventive Veterinary Medicine and Animal Reproduction of FCAV/UNESP, Jaboticabal campus, with the children of the “Lar Caminho” municipal shelter. Educational activities were undertaken to raise the awareness of the children concerning themes such as responsible ownership, leptospirosis, and rabies. The project was successful, resulting in good interaction among the participants and fulfilling the main objective of information transfer. In addition, it was an opportunity to implement the inseparable triad of “research, education, and extension” that should never be ignored as one of the basic principles of the university.

Teniendo en cuenta que el principio de Educación para la Salud es la transmisión de información a la comunidad, y teniendo en cuenta la importante contribución que los niños ofrecen como multiplicadores de la sociedad del conocimiento, el proyecto "Navidad del EducaPrev" tuvo como objetivo la integración de los estudiantes de posgrado del Departamento de Medicina Veterinaria Preventiva y Reproducción Animal FCAV / UNESP / Jaboticabal / SP, con niños menores de un municipio, para llevar a cabo actividades educativas que permitieron a la concientización de los niños sobre temas importantes como el cuidado responsable con los animales, la leptospirosis y la rabia. El proyecto fue un éxito y dió lugar a una gran socialización entre los interesados y alcanzó el objetivo de la transferencia de información, más allá de la posibilidad de cumplir tríada inseparable "Investigación, Educación y Extensión", que nunca debe ser separada dentro de los principios básicos de la Universidad.

Tendo em vista que o princípio de Educação em Saúde é o repasse de informações à comunidade, e levando-se em conta a importante colaboração que as crianças oferecem como multiplicadores de conhecimento à sociedade, o projeto “Natal do EducaPrev” teve como objetivo a integração dos alunos de pós-graduação do Departamento de Medicina Veterinária Preventiva e Reprodução Animal da FCAV/Unesp/Jaboticabal/SP, com os crianças de um abrigo do município, para a realização de atividades educativas que possibilitaram a conscientização  das crianças sobre temas importantes como guarda responsável de animais, leptospirose e raiva. O projeto foi um sucesso, tendo resultado em uma ótima socialização entre os envolvidos e atingindo o intuito de transferência de informações, além da possibilidade do cumprimento da tríade indissociável “Pesquisa; Ensino e Extensão”, que nunca deve ser desvinculada dentro dos princípios básicos da Universidade.
Educaprev christmas: health education in a shelter in jaboticabal/sp
Navidad del educaprev: educación para la salud en un refugio del condado de jaboticabal/sp
Keywords: Responsible ownership; Zoonosis; Veterinary public health; Cuidado Responsable; Zoonosis; Salud pública veterinaria; Educação; Guarda responsável; Zoonoses; Saúde pública veterinária